Daftar Variasi Nama Gedhang (Pisang) dalam Dialek Brebes Selatan Bahasa Jawa sebagai Bahan Ajar Pendukung untuk Mata Kuliah Biologi Farmasi - Wilda Putri Festiyanti; Febia Citraeni Rusdaita; Arinda Nur Cahyani; Elma Ertian Rinaldi; Elsi Salwa Al-Humairoh; Widi Anti (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2026)
This research documents and analyzes the variations of banana (gedhang) names in the Southern Brebes dialect of the Javanese language from a sociolinguistic viewpoint. The study explores how language reflects social and cultural realities within a local community. Indonesia’s vast cultural and linguistic diversity makes the study of regional registers essential for understanding how people use language to represent their environment. The Southern Brebes area shows a wide range of banana varieties, each identified by distinct local names that convey information about their physical traits, uses, and cultural significance. These linguistic variations also have educational potential, particularly as supplementary materials for courses such as Pharmaceutical Botany. The research further examines social, cultural, and environmental factors shaping the creation and usage of these names. Findings are expected to enhance understanding of the Javanese lexical system especially the Southern Brebes dialect and to highlight the deep connection between language, culture, and identity. Ultimately, this study contributes to the preservation of local linguistic and cultural heritage.